Towards Accountability: A Primer on the Space Debris Problem and an Overview of the Legal Issues Surrounding It - William Schonberg (Aerospace)
Since 1957, the near-Earth population of trackable space objects has grown in number to over 36,000. Of these 36,000+ trackable objects now in low Earth orbit, just a few thousand are working spacecraft. The rest are Earth-orbiting objects which are no longer operational and are considered to be space junk. Because this junk can no longer receive maneuvering commands from its Earth-based owners, the survivability of other spacecraft traveling through or operating in Earth orbit can be jeopardized by the impacts of any number of pieces of this space junk, whose origins can usually be traced back to defunct satellites. As a result, a major design parameter for Earth-orbiting spacecraft is the possibility of such high-speed impacts and the damage they can cause. Furthermore, several private companies are now launching several thousand spacecraft into Earth orbit, many of which are satellites built for communication purposes. Other satellites have been launched to expand the reach of the World Wide Web and to provide better tools for disaster management. Two questions quickly become evident, namely, what is the beneficial purpose of these large satellite constellations, and what are some of the deleterious consequences of their proliferation? Numerous topics related to space debris will be discussed in this paper, including issues in space law that concern the growing problem of orbital debris. In the end, several areas of concern will be noted that are vital to the continuing presence of humans in near-Earth space and must be addressed as the near-Earth orbital environment becomes more congested and space traffic management becomes more difficult.